Contemporary application of categorizing zakat recipients under Riqab - Ismail, Yusof; Awang, Abdul Bari; Sarif, Suhaimi Mhd (World Fatwa Management and Research Institute (INFAD) at Universiti Sains Islam Malaysia (USIM), 2019)
Contemporary approach of categorizing zakat recipients under Riqab or slavery is essential to reflect the current contexts. Thus, the categorization certainly requires adaptation and application. In the old days, slavery was apparent in the society. It is not in today’s context. Nevertheless, slavery may happen in different forms and shapes. There are abundant fiqh literatures with some novel ideas of practical implications to contemporary Muslim societies. This study serves as preliminary attempt to seek the opinions of Muslim respondents on how the contemporary contexts of slavery to entitle them categorised under Riqab. The study developed a preliminary instrument and tested it on Muslim undergraduates of a public university in Malaysia who are non-specialists in Shari’ah, Fiqh, or Usul al-Fiqh. By using nine statements with a Likert-like scale, and one open-ended question, the study was able to obtain an acceptable reliability (Cronbach reliability of 0.704). Data analysis using t-test shows that male and female respondents (n=70) did not differ significantly in their views, except for “freeing a prisoner of war” (p-value .002). The rating by the respondents on eligible riqab recipients ranked “freeing a person from an oppressive ruler” (4.09/5.00), and “freeing a prisoner of war” (4,03/5.00) among the top, whereas paying off a person’s debt (3.29/5.00) the last. A significant contribution of the research is perhaps the development of the instrument which may be replicated on other types of respondents.